On the half-metallicity of Co2FeSi Heusler alloy: Point-contact Andreev reflection spectroscopy and ab initio study - Makinistian, L.; Faiz, Muhammad M.; Panguluri, Raghava P.; Balke, Benjamin; Wurmehl, Sabine; Felser, Claudia; Albanesi, E. A.; Petukhov, A. G.; Nadgorny, Boris (Physical Review B - Condensed Matter and Materials Physics, 2013)
Co2FeSi, a Heusler alloy with the highest magnetic moment per unit cell and the highest Curie temperature, has largely been described theoretically as a half-metal. This conclusion, however, disagrees with point contact Andreev reflection (PCAR) spectroscopy measurements, which give much lower values of spin polarization, P. Here, we present the spin polarization measurements of Co2FeSi by the PCAR technique, along with a thorough computational exploration, within the DFT and a GGA+U approach, of the Coulomb exchange U parameters for Co and Fe atoms, taking into account spin-orbit coupling. We find that the orbital contribution (mo) to the total magnetic moment (mT) is significant, since it is at least 3 times greater than the experimental uncertainty of mT. The account of mo radically affects the acceptable values of U. Specifically, we find no values of U that would simultaneously satisfy the experimental values of the magnetic moment and result in the half-metallicity of Co2FeSi. On the other hand, the ranges of U that we report as acceptable are compatible with spin polarization measurements (ours and the ones found in the literature), which all are within approximately the 40-60 % range. Thus, based on reconciling experimental and computational results, we conclude that (a) spin-orbit coupling cannot be neglected in calculating Co2FeSi magnetic properties, and (b) Co2FeSi Heusler alloy is not half-metallic. We believe that our approach can be applied to other Heusler alloys such as Co2FeAl. © 2013 American Physical Society.
CRIS-Team Scopus Importer:2023-03-20